Histone Deacetylase Isoforms Differentially Modulate Inflammatory and Autoantibody Responses in a Mouse Model of Myasthenia Gravis - Bahauddin, Afrin; Ivannikov, Maxim; Wang, Zhongying; Jamaluddin, Mohammad; Curtis, Kyra; Ibtehaj, Naazneen; Yeager, Linsey; Soong, Lynn; Fang, Xiang; Huda, Ruksana (Frontiers in Neurology, 2022)
Myasthenia gravis (MG) is an autoimmune disease characterized by chronic muscle fatigue and weakness caused by autoantibodies and complement-mediated damage at neuromuscular junctions. Histone deacetylases (HDACs) are crucial epigenetic regulators of proinflammatory gene expression; however, it is unclear whether HDACs modulate chronic inflammation or autoantibody production associated with MG pathogenesis. We examined expression profiles and serum levels of key inflammatory cytokines (IL-6 and IL-21) and acetylcholine receptor (AChR)-specific autoantibodies following pharmacological inhibition of key HDAC isoforms in a mouse model of MG. We found that HDAC inhibition significantly reduced the production of IL-6, but not IL-21, in AChR-stimulated PBMCs and splenocytes. Trichostatin (pan-HDAC inhibitor) treatment of MG-PBMCs also exhibited reduced production of induced IL-6. Although HDAC1 inhibition lowered IL-6 levels the most, HDAC2 inhibition depleted intracellular IL-6 and markedly reduced serum anti-AChR IgG2b. The transcriptomic profiling and pathway mapping also revealed that autoimmunity-linked, major cell signaling pathways were differentially altered by HDAC1/2 inhibition. HDAC inhibition-mediated reduction in IL-6 and autoantibody levels also correlated with milder disease and preservation of muscle AChR in the treated mice. Overall, our findings revealed isoform-specific functional variance of HDACs in reducing inflammation and identified HDAC-regulated many genes underlying specific inflammatory and autoantibody pathways in EAMG. Thus, the study provides a rationale for further research to evaluate the HDACs or their gene targets as a potential adjunct treatment for MG.